Student Engagement in Adolescence: A Scoping Review of Longitudinal Studies 2010–2020. (15th May 2021) - Salmela‐Aro, Katariina; Tang, Xin; Symonds, Jennifer; Upadyaya, Katja
Abstract : We systematically mapped and analyzed the longitudinal research on adolescent student engagement published during 2010–2020. A total of 104 studies of 104, 304 adolescents met inclusion criteria. Studies were mainly conducted in North America (43%) or Europe (34%). Over half studied engagement across one or more years. Most studies (93%) focused on antecedents of engagement rather than outcomes of engagement (38%). Data were commonly collected using self‐report questionnaires (87%) and analyzed using path, growth, and cross‐lagged models. Studies mainly examined engagement in classroom activities, school, or schoolwork; and focused on behavioral engagement (70%), followed by emotional (61%), then cognitive engagement (35%). No studies used a specific theory of engagement development, but instead referred to self‐determination, ecological systems, and stage‐environment fit theories.